'Beasts, burrowers and birds': The enactment of researcher identities in UK business schools. Issue 3 (July 2014) - Bell, Emma; Clarke, Daniel W
In this article, we suggest that management research constitutes a field of practice that is made practically intelligible through embodied enactment. This relies on imagination, constructing modes of belonging within communities of management research practice. Undergraduate students constitute a significant audience towards whom these self-presentational performances are directed. Our analysis is based on findings from four UK business schools where students participated in a free drawing and focus group exercise and were asked to visualize a management researcher. Through identification of three dominant animal metaphors of management research practice, we explore the symbolic relations whereby a prevailing image of the management researcher, as untouchable, solitary, aggressive, competitive and careerist, is socially constructed. We argue that this competitive, self-interested impression of research is detrimental to ethical, critically reflexive, reciprocal and participatory modes of research, and to the development of management research as a broadly inclusive system of social learning.